Entrepreneurship Education Based on Islamic Values in Integrated Islamic Schools: A Systematic Literature Review and Applicational Design - Raihanah, Raihanah; Yusuf, Mahmud; Rahmah, Rahmah; Azieza, Nayla (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to map previous studies from reputable national and international journals related to Islamic value-based entrepreneurship education and to create an application design that can be applied in Integrated Islamic Schools. The method used in this study is a systematic literature review with data collection using Publish or Perish, assessment using https://www.scimagojr.com/ and https://sinta.kemdikbud.go.id/,and analysis using Chatbot Generative Pre-trained Transformer (Chat GPT). The results of this study indicate that since 2015-2025, at least 12 journal articles indexed by Scopus and Sinta 2 were found discussing Islamic value-based entrepreneurship education with details of 1 article indexed Q1, 2 articles indexed Q3, 1 article indexed Q4, and 8 articles indexed Sinta 2. By elaborating on the important points of the 12 journal articles, we created an application design for Islamic value-based entrepreneurship education in Integrated Islamic Schools, in the form of; 1) Stages consisting of elementary, junior high, and senior high levels, 2) Materials consisting of theory, soft skills, and hard skills, 3) Methods consisting of conventional learning, training, as well as project-based learning and experiential learning, 4) Facilities consisting of School Business Units and start-up partners/sharia companies, 5) The combination of all these designs is ultimately expected to be able to shape students into creative, innovative, optimistic Muslim entrepreneurs based on Islamic values.